Quantum chemical mass spectrometry: ab initio prediction of electron ionization mass spectra and identification of new fragmentation pathways. (5th July 2016) - Cautereels, Julie; Claeys, Magda; Geldof, Davy; Blockhuys, Frank
Abstract : The electron ionization mass spectra of four organic compounds are predicted based on the results of quantum chemical calculations at the DFT/B3LYP/6‐311 + G* level of theory. This prediction is performed ' ab initio ', i.e. without any prior knowledge of the thermodynamics or kinetics of the reactions under consideration. Using a set of rules determining which routes will be followed, the fragmentation of the molecules' bonds and the complete resulting fragmentation pathways are studied. The most likely fragmentation pathways are identified based on calculated reaction energies ΔE when bond cleavage is considered and on activation energies ΔE ‡ when rearrangements are taken into account; the final intensities of the peaks in the spectrum are estimated from these values. The main features observed in the experimental mass spectra are correctly predicted, as well as a number of minor peaks. In addition, the results of the calculations allow us to propose fragmentation pathways new to empirical mass spectrometry, which have been experimentally verified using tandem mass spectrometry measurements. Copyright © 2016 John Wiley & Sons, Ltd.